KAPASITAS KELOMPOK TANI DI DESA UUWAN KECAMATAN DUMOGA BARAT KABUPATEN BOLAANG MONGONDOW - MANITIK, ENGLIN FERLINA; KIYAI, BURHANUDDIN; RURU, JOORIE (JURNAL ADMINISTRASI PUBLIK, 2021)
The capacity of farmer groups is one of the things that can help the welfare of the existing village ofUuwan. The existence of ani group in Bolaang Mongondow Regency basically greatly affects theimprovement of the economy and the welfare of the community, this is seen from the number ofworkers and the size of land in the sector. Empowerment of farmers is all efforts to improve theability of farmers to carry out better farming activities through education and training, counseling andassistance in developing systems and means of marketing for cultivated agricultural products andguaranteeing the extent of agricultural land, easy access to science, technology and information andstrengthening farmer institutions. The results of the 5 existing informants can be concluded that thewelfare of the Uuwan village community is good and not a little from agricultural products. And also fromthe social aspect, In Uuwan village, social life in the community is already high. And in education also inUuwan Village, many have been educated up to a Bachelor's degree compared to a few years ago foronly a few high school graduates, but now many parents who are farmers are able to send their childrento the strata 1 level even many are already working .Keywords: Capacity, Farmer Groups, Empowerment